Challenges faced by e-pjj students in UiTM Sarawak / Khadtizah Khamsyiah Berawi & Siti Rubiah Mohd Rusli - Berawi, Khadtizah Khamsyiah; Mohd Rusli, Siti Rubiah (2008)
This research paper is about challenges faced by e-leaming student (e-pjj) students in UiTM Sarawak. Through this research we want to determine understanding ofthe concept of e-leaming among the students. Besides that, we also want to determine the influence of the learning environment toward student’s readiness and to analyze the use of ICT among the e-leaming students. Through the findings that we get from this research, it can be useful for the management and the lecturers in order to improve the effectiveness of e-leaming in UiTM Sarawak. Besides that, we hope this research will also be helpful for the policy maker in order to create and design the policy regarding e-leaming.